Zombies at large? Corporate debt overhang and the macroeconomy - Òscar Jordà; Martin Kornejew; Moritz Schularick; Alan M. Taylor (Federal Reserve Bank of New York, 2020)
With business leverage at record levels, the effects of corporate debt overhang on growth and investment have become a prominent concern. In this paper, we study the effects of corporate debt overhang based on long-run cross-country data covering the near-universe of modern business cycles. We show that business credit booms typically do not leave a lasting imprint on the macroeconomy. Quantile local projections indicate that business credit booms do not affect the economy's tail risks either. Yet in line with theory, we find that the economic costs of corporate debt booms rise when inefficient debt restructuring and liquidation impede the resolution of corporate financial distress and make it more likely that corporate zombies creep along.
Keywords: E44; G32; G33; N20; 330; corporate debt; business cycles; local projections